Enhanced lignin removal and enzymolysis efficiency of grass waste by hydrogen peroxide synergized dilute alkali pretreatment. (April 2020) - Yan, Xing; Cheng, Jing-Rong; Wang, Yu-Tao; Zhu, Ming-Jun
Graphical abstract: Highlights: Dilute NaOH supplemented with H2 O2 pretreatment was successfully employed to GW. The pretreated GW showed high holocellulose recovery under mild condition. The process exhibited synergistic effect on lignin removal and enzymolysis. High titers of ethanol from the pretreated GW was achieved by SSCF. Abstract: Pretreatment process plays a key role in biofuel production from lignocellulosic feedstocks. A study on dilute NaOH pretreatment supplemented with H2 O2 under mild condition was conducted to overcome the recalcitrance of grass waste (GW). The optimized process could selectively increase lignin removal (73.2%), resulting in high overall recovery of holocellulose (73.8%) as well as high enzymolysis efficiency (83.5%) compared to H2 O2 or NaOH pretreatment. The analyses by Scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) revealed that supplementary H2 O2 disrupted the structure of GW to facilitate the removal of lignin by NaOH, and exhibited synergistic effect on lignin removal and enzymolysis with dilute NaOH. Moreover, high titer of ethanol (100.7 g/L) was achieved by SSCF on 30% (w/v) pretreated GW loading. The present study suggests that the established synergistic pretreatment is a simple, efficient, and promising process for GW biorefinery.